2019
DOI: 10.1177/0018720819874160
|View full text |Cite
|
Sign up to set email alerts
|

Team Physiological Dynamics: A Critical Review

Abstract: Objective: Review the use of physiological measurement in team settings and propose recommendations to improve the state of the science. Background: New sensor and analytical capabilities enable exploration of relationships between team members’ physiological dynamics. We conducted a review of physiological measures used in research on teams to understand (1) how these measures are theoretically and operationally related to team constructs and (2) what types of validity evidence exist for physiological measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(74 citation statements)
references
References 78 publications
(279 reference statements)
4
70
0
Order By: Relevance
“…Our methods mirror recent search approaches in literature reviews reported in this journal (e.g., Kazi et al, 2019;Patterson, 2018). The criteria for inclusion in the current review were fourfold.…”
Section: Methodsmentioning
confidence: 99%
“…Our methods mirror recent search approaches in literature reviews reported in this journal (e.g., Kazi et al, 2019;Patterson, 2018). The criteria for inclusion in the current review were fourfold.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, we encourage future research efforts to consider a wider range of possible well-being indicators. For example, objective data that indicate stress (e.g., saliva cortisol concentration, heart-rate variability, blood-pressure; for a review of physiological measurement in team settings see Kazi et al, 2019) may supplement self-reported data on health and well-being.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Landon et al ( 2019 ) provide a wide ranging and integrative review of the topic as it relates to performance within ICE settings, and Stevens et al ( 2019 ) provide a remarkable example of how patterns of physiological activation across team members can be identified and used to predict team outcomes. These articles are exemplars of the emerging area of team physiological dynamics, which has accelerated rapidly in recent years (Kazi et al, 2019 ). The science of teams can progress quickly in this area by exploring related areas of social (Cacioppo et al, 2000 ) and organizational neuroscience (Becker et al, 2011 ) and interpersonal physiological dynamics outside of work team contexts (Palumbo et al, 2017 ).…”
Section: Team Science Now Incorporates Ever Broader Ranges Of Individmentioning
confidence: 99%